Mobile Computing - Hamilton Ortiz, Jesus (IntechOpen, 2020)
Mobile computing is defined as the union between humans and mobile devices that allows people to be connected to the Internet through a network in order to transmit and receive information. This book presents a vision of the present and future of mobile computing. It identifies and examines the most pressing research issues in the field. Comprising chapters by leading researchers and academics, this volume includes recent publications in key areas of interest, including Flying Ad-Hoc Networks (FANETs), Vehicular Ad-Hoc Networks (VANETs), 5G, energy-efficient networks, localization in mobile networks, algorithms of mobile core networks, user interfaces, metabolic health analysis, and many others. This volume is suitable as a text for graduate students and professionals in the industrial sector and general engineering areas.